ADIPONECTIN ACTIVITY IN ACUTE VIRAL HEPATTOBI - Suryadarma, I Gusti Agung (journal of internal medicine, 2012)
The mechanisms of hepatocellular necrosis in acute viral hepatitis, primarily through cytopathic immune mechanisms, however the processes of hepatic parenchyma necrosis also might be secondarily involved the roles of cytopathic non-immune mechanisms. Once of the defend mechanisms to the hepatic viral infection is through the releases of adiponectin. Adiponectin is a hormone secreted by adipocytes. The protective effect of adiponectin against liver injury likely involve multiple mechanisms, especially to the ability effects of adiponectin as a anti-inflammatory cytokines. Thus, decreased of the adiponectin concentration <10 mg/dl in the acute viral hepatitis, especially Hepatitis B and C perhaps as the early biomarkers of possibility progression to the chronic hepatitis.
Keywords: adiponectin, acute viral hepatitis.